Growth regulation in tip-growing cells that develop on the epidermis - Honkanen, S; Dolan, L (Elsevier, 2017)
Plants develop tip-growing extensions-root hairs and rhizoids-that initiate as swellings on the outer surface of individual epidermal cells. A conserved genetic mechanism controls the earliest stages in the initiation of these swellings. The same mechanism controls the formation of multicellular structures that develop from swellings on epidermal cells in early diverging land plants. Details of the molecular events that regulate the positioning of the swellings involve sterols and phosphatidylinositol phosphates. The final length of root hairs is determined by the intensity of a pulse of transcription factor synthesis. Genes encoding similar transcription factors control root hair development in cereals and are potential targets for crop improvement.